2018
DOI: 10.1126/sciadv.aar3321
|View full text |Cite
|
Sign up to set email alerts
|

Chondrules as direct thermochemical sensors of solar protoplanetary disk gas

Abstract: Cathodoluminescence reveals structures indicative of gas-assisted epitaxial growth during chondrule melt crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 46 publications
11
56
0
Order By: Relevance
“…3, Table S1). Such oscillatory zonings have previously been reported from cathodoluminescence maps (Steele et al, 1985;Steele, 1986Steele, , 1995Libourel and Portail, 2018) and phosphorus X-ray maps (McCanta et al, 2016), and one Allan Hills A81189 (EH3) chondrule even showed strong Fo 75-97 oscillations in its olivine phenocrysts (Lusby et al, 1987).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…3, Table S1). Such oscillatory zonings have previously been reported from cathodoluminescence maps (Steele et al, 1985;Steele, 1986Steele, , 1995Libourel and Portail, 2018) and phosphorus X-ray maps (McCanta et al, 2016), and one Allan Hills A81189 (EH3) chondrule even showed strong Fo 75-97 oscillations in its olivine phenocrysts (Lusby et al, 1987).…”
Section: Resultssupporting
confidence: 73%
“…In this model, relict grains are thus direct proxies of the first solids formed in the SPD, whereas host chondrule crystals represent thermochemical and isotopic sensors of the surrounding gas during chondrule formation. At the same time, (Libourel and Portail, 2018) interpreted type I chondrule cathodoluminescence zoning patterns similar to ours in X-ray maps as the result of crystallization from Ca-Alrich melts produced in dense environments of the SPD. Clearly, the study of such zonings is nascent and will provide valuable insights into chondrule formation.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The absence of metal grains in completely molten chondrule precursors was theoretically predicted by Uesugi et al (2005Uesugi et al ( , 2008. In addition, the unique occurrence of metal grains in the core region of magnesium-rich olivine crystals of porphyritic chondrules suggests that the metal grains act as seeding agents during the crystal growth of the olivine crystals in porphyritic chondrules (Libourel & Portail 2018), and the difference in the textures of porphyritic or barred olivine chondrules is linked to the presence/absence of iron-nickel metal grains.…”
Section: Metal Grainsmentioning
confidence: 87%
“…Such accretion mechanisms are of specific interest as they may have played an important role in terrestrial planet formation (e.g., Bollard et al, ; Cuzzi et al, ; Jacobsen & Walsh, ; Johansen et al, ; Levison et al, ), since chondrule‐rich accretion can potentially explain volatile and moderately volatile element abundances in the BSE and BE (e.g., Amsellem et al, ; Hewins & Herzberg, ; Mahan, Siebert, et al, ; Righter et al, ), especially in the absence of appreciable volatile loss from Earth and other terrestrial bodies during accretion (e.g., Canup et al, ; Stewart et al, ). Moreover, chondrules likely provide a reliable record of the conditional and compositional evolution of the solar system during the planet‐forming epoch (Libourel & Portail, ; Mahan, Moynier, et al, ). In the following models, both the size and volatile contents of Earth's accreting materials increase with time, culminating in a relatively volatile‐rich, large impactor corresponding to 9.5% M E toward the end of accretion.…”
Section: Discussionmentioning
confidence: 99%